Testing viscous disc theory using the balance between stellar accretion and external photoevaporation of protoplanetary discs - Winter, Andrew J.; Ansdell, Megan; Haworth, Thomas; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society. Letters, 2020)
The nature and rate of (viscous) angular momentum transport in protoplanetary discs (PPDs) have important consequences for the formation process of planetary systems. While accretion rates on to the central star yield constraints on such transport in the inner regions of a PPD, empirical constraints on viscous spreading in the outer regions remain challenging to obtain. Here, we demonstrate a novel method to probe the angular momentum transport at the outer edge of the disc. This method applies to PPDs that have lost a significant fraction of their mass due to thermal winds driven by UV irradiation from a neighbouring OB star. We demonstrate that this external photoevaporation can explain the observed depletion of discs in the 3-5 Myr old sigma Orionis region, and use our model to make predictions motivating future empirical investigations of disc winds. For populations of intermediate-age PPDs, in viscous models we show that the mass flux outwards due to angular momentum redistribution is balanced by the mass-loss in the photoevaporative wind. A comparison between wind mass-loss and stellar accretion rates therefore offers an independent constraint on viscous models in the outer regions of PPDs.